Engendering Transnational Transgressions
1 online resource
Keywords: Engendering Transnational Transgressions reclaims the transgressive side of feminist history, challenging hegemonic norms and the power of patriarchies. Through the lenses of intersectionality, gender analysis, and transnational feminist theory, it addresses the political in public and intimate spaces. The book begins by highlighting the transgressive nature of feminist historiography. It then divides into two parts--Part I,Intimate Transgressions: Marriage and Sexuality, examines marriage and divorce as viewed through a transnational lens, and Part II, Global Transgressions: Networking for Justice and Peace, considers political and social violence as well as struggles for relief, redemption, and change by transnational networks of women. Chapters are archivally grounded and take a critical approach that underscores the local in the global and the significance of intersectional factors within the intimate. They bring into conversation literatures too often separated: history of feminisms and anti-war, anti-imperial/anti-fascist, and related movements, on the one hand, and studies of gender crossings, marriage reconstitution, and affect and subjectivities, on the other. In so doing, the book encourages the reader to rethink standard interpretations of rights, equality, and recognition. This is the ideal volume for students and scholars of Women's and Gender History and Women's and Gender Studies, as well as International, Transnational, and Global History, History of Social Movements, and related specialized topics.